Water Purifying Capacity of Natural Riverine Wetlands in Relation to Their Ecological Quality - Sileshi, Adey; Awoke, Aymere; Beyene, Abebe; Stiers, Iris; Triest, Ludwig (Frontiers in Environmental Science, 2020)
Wetlands are among the crucial nature based solutions for river water purification. The ecological integrity of this multi-purpose ecosystem could be disrupted due to overloading of nutrients and other pollutants. We investigated the water purifying effect and ecological integrity of three natural riverine wetlands (urban downstream in Boye and urban upstream in Fisho and Kitto). We sampled water, macroinvertebrates, and diatoms, to compare sites before joining the wetland, within the wetland and after passing through the wetland. The lower concentration of nutrients, and BOD in sites after joining the wetland showed the presence of pollution attenuation. Macroinvertebrate and diatom based bio-indices depicted higher biodiversity and lower relative abundance of tolerant taxa in sites after joining the wetland, which implicated the potential of studied wetlands to reduce pollutants and sustain biodiversity. The wetland fed by heavily polluted streams showed the most degraded ecological quality compared to the other two, fed by less polluted streams. An RDA model visualized this pollution gradient among sites. Generally, this study confirmed the potential of natural wetlands to attenuate nutrients and organic pollutants and sustain biodiversity. However, when the incoming water is heavily degraded, the retention of pollutants seriously affect the wetland’s ecological integrity.